Determinants of functioning and health-related quality of life after vestibular stroke - Schuhbeck, Franziska; Strobl, Ralf; Conrad, Julian; Möhwald, Ken; Jaufenthaler, Patricia; Jahn, Klaus; Dieterich, Marianne; Grill, Eva; Zwergal, Andreas (Frontiers in Neurology, 2022)
Background Stroke accounts for 5–10% of all presentations with acute vertigo and dizziness. The objective of the current study was to examine determinants of long-term functioning and health-related quality of life (HRQoL) in a patient cohort with vestibular stroke. Methods Thirty-six patients (mean age: 66.1 years, 39% female) with an MRI-proven vestibular stroke were followed prospectively (mean time: 30.2 months) in the context of the EMVERT (EMergency VERTigo) cohort study at the Ludwig-Maximilians Universität, Munich. The following scores were obtained once in the acute stage (<24 h of symptom onset) and once during long-term follow-up (preferably >1 year after stroke): European Quality of Life Scale-five dimensions-five levels questionnaire (EQ-5D-5L) and Visual Analog Scale (EQ-VAS) for HRQoL, Dizziness Handicap Inventory (DHI) for symptom severity, and modified Rankin Scale (mRS) for general functioning and disability. Anxiety state and trait were evaluated by STAI-S/STAI-T, and depression was evaluated by the Patient Health Questionnaire-9 (PHQ-9). Voxel-based lesion mapping was applied in normalized MRIs to analyze stroke volume and localization. Multiple linear regression models were calculated to determine predictors of functional outcome (DHI, EQ-VAS at follow-up). Results Mean DHI scores improved significantly from 45.0 in the acute stage to 18.1 at follow-up (p < 0.001), and mean mRS improved from 2.1 to 1.1 (p < 0.001). Mean HRQoL (EQ-5D-5L index/EQ-VAS) changed from 0.69/58.8 to 0.83/65.2 (p = 0.01/p = 0.11). Multiple linear regression models identified higher scores of STAI-T and DHI at the time of acute vestibular stroke and larger stroke volume as significant predictors for higher DHI at follow-up assessment. The effect of STAI-T was additionally enhanced in women. There was a significant effect of patient age on EQ-VAS, but not DHI during follow-up. Conclusion The average functional outcome of strokes with the chief complaint of vertigo and dizziness is favorable. The most relevant predictors for individual outcomes are the personal anxiety trait (especially in combination with the female sex), the initial symptom intensity, and lesion volume. These factors should be considered for therapeutic decisions both in the acute stage of stroke and during subsequent rehabilitation.